Bankruptcy and Firm Dynamics : The Case of the Missing Firms - Rodriguez-Delgado, Jose Daniel (IMF Working Papers; Working Paper ;, 2010)
Financial frictions have been documented as an important determinant of firm dynamics. In this paper I model bankruptcy procedures, liquidation in particular, as an institutional feature that affects both sides of financial transactions. I construct a model of firm dynamics that generate endogenous borrowing limits and I find that a) inefficient bankruptcy procedures can have quantitatively important aggregate effects, but more importantly; b) that such effects would not be directly visible in the firms that industrial censuses and surveys focus on. I conclude that to capture the effects of the legal framework we need to look beyond the existing firms.